How can we feed nine billion people while reducing GHG emissions? - Campbell, Bruce M.; Vermeulen, Sonja J.; Hansen, James; Jarvis, Andy; Thornton, Philip K.; Wollenberg, Eva Karoline (2011)
Global warming will have far-reaching consequences for agriculture that will dispropotionately affect poor and marginalized groups who depend on agriculture for their livelihoods and have a lower capacity to adapt. Sustainable food security in a world of growing population and changing dieats is a major challenge under climate change.